2007
DOI: 10.1681/asn.2007010067
|View full text |Cite
|
Sign up to set email alerts
|

Prehypertension Increases the Risk for Renal Arteriosclerosis in Autopsies

Abstract: Information regarding the association between prehypertension BP level and renal arteriosclerosis is limited. In 652 consecutive population-based autopsy samples without hypertension treatment before death, the relationship between the severity of renal arteriosclerosis and BP levels classified according to the criteria of the Seventh Report of the Joint National Committee on Prevention, Detection, Evaluation, and Treatment of High Blood Pressure was examined. The age-and gender-adjusted frequencies of renal a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
32
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(38 citation statements)
references
References 21 publications
3
32
0
1
Order By: Relevance
“…18 Much as in other previous reports worldwide, [14][15][16] older age, higher prevalence of men, and obesity or obesity-related metabolic abnormalities were more prevalent in subjects with prehypertension than those with optimal BP (Table 2). These characteristics could partly explain the cardiovascular risk of prehypertesion; 15-17 however, our data show that the association between CKD and prehypertension with high-normal BP in men is independent of these confounders.…”
Section: Discussion Prehypertension and Ckdsupporting
confidence: 65%
“…18 Much as in other previous reports worldwide, [14][15][16] older age, higher prevalence of men, and obesity or obesity-related metabolic abnormalities were more prevalent in subjects with prehypertension than those with optimal BP (Table 2). These characteristics could partly explain the cardiovascular risk of prehypertesion; 15-17 however, our data show that the association between CKD and prehypertension with high-normal BP in men is independent of these confounders.…”
Section: Discussion Prehypertension and Ckdsupporting
confidence: 65%
“…Prehypertension and hypertension were associated in most cases with at least two additional cardiovascular risk factors thus enhancing the odds to develop cardiovascular events [9] [19] [20] [42] [43]. The risk in subjects with prehypertension has been attributed to endothelial dysfunction, increased level of pro-inflammatory cytokines and gamma glutamyl-transferase, oxidative stress, and structural remodelling of the myocardium in comparison to subjects with blood pressure in the normal range [9] [23] [44]- [47]. Unlike other studies [11] [37] [48] [49] the rates of diabetes mellitus were similar in our three blood pressure categories whereas in accordance with most reports [18] Our results should be interpreted within the limitations of the present work.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, aortic dilation assessed by magnetic resonance imaging and intravascular ultrasound was significantly reduced in the prehypertensive group (Toikka et al 2002). In the prehypertensive group, increased CIMT, new development of atherosclerosis, and reduced diastolic function were observed (Ninomiya et al 2007). In addition, a longitudinal study of prehypertensive patients found that they were at high risk for cardiovascular diseases and stroke (Liszka et al 2005;De Marco et al 2009).…”
Section: Discussionmentioning
confidence: 90%
“…In addition, decreased arterial elasticity, increased CIMT and increased development of atherosclerosis were observed in the prehypertension group (Ninomiya et al 2007). Therefore, hypertension increases the risk, not only for cardiovascular diseases, but also for cerebrovascular diseases (Hsia et al 2007;De Marco et al 2009).…”
Section: Introductionmentioning
confidence: 93%